2021
DOI: 10.2337/dc20-2960
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-Wide Association Study Reveals Methylation Loci Associated With Offspring Gestational Diabetes Mellitus Exposure and Maternal Methylome

Abstract: Objective: Gestational diabetes mellitus (GDM) is associated with a future offspring risk for the development of obesity and insulin resistance in Gestational diabetes mellitus (GDM) is associated with an increased risk of obesity and insulin resistance in offspring later in life, which might be explained by epigenetic changes in response to maternal hyperglycaemic exposure. Research Design and Methods:We explored the association of GDM exposure on maternal blood and newborn cord-blood methylation of 536 mothe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Seven cohorts with cord blood DNAm and fasting glycemic data in midpregnancy participated in the meta-analyses ( Table 1 and Supplementary Material ). These cohorts were from Southeast Asia (Singapore: Growing Up in Singapore Towards healthy Outcomes [GUSTO] [ 14 ]), North America (Canada: Genetics of Glucose regulation in Gestation and Growth [Gen3G] [ 15 ], U.S.: Healthy Start [ 16 ]), and Europe (Finland: the Finnish Gestational Diabetes [FinnGeDi] Study [ 7 , 17 ] and Prediction and Prevention of Preeclampsia and Intrauterine Growth Restriction [PREDO] study [ 18 ], France: EDEN [ 19 ], and Belgium: the ENVIRonmental influence ON early AGEing [ENVIRONAGE] [ 20 ]). One cohort, in the Generation R Study ( 21 ) (the Netherlands), had nonfasting glycemic data (included in a secondary analysis).…”
Section: Methodsmentioning
confidence: 99%
“…Seven cohorts with cord blood DNAm and fasting glycemic data in midpregnancy participated in the meta-analyses ( Table 1 and Supplementary Material ). These cohorts were from Southeast Asia (Singapore: Growing Up in Singapore Towards healthy Outcomes [GUSTO] [ 14 ]), North America (Canada: Genetics of Glucose regulation in Gestation and Growth [Gen3G] [ 15 ], U.S.: Healthy Start [ 16 ]), and Europe (Finland: the Finnish Gestational Diabetes [FinnGeDi] Study [ 7 , 17 ] and Prediction and Prevention of Preeclampsia and Intrauterine Growth Restriction [PREDO] study [ 18 ], France: EDEN [ 19 ], and Belgium: the ENVIRonmental influence ON early AGEing [ENVIRONAGE] [ 20 ]). One cohort, in the Generation R Study ( 21 ) (the Netherlands), had nonfasting glycemic data (included in a secondary analysis).…”
Section: Methodsmentioning
confidence: 99%
“…Global DNAm is altered during hyperglycemia ( 34 , 35 ), and increased global methylation in placental tissue has been associated with GDM ( 36 , 37 ). However, there are limited data describing DNAm in the peripheral blood of patients with GDM, and the results are inconclusive ( 16-19 , 21 , 22 , 38 , 39 ). Small sample sizes and the absence of reproducibility or confirmatory cohorts have been the main weaknesses in most studies ( 16-18 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on Black South African women, global DNAm in peripheral blood was found not to be associated with GDM, which was contrary to the authors’ hypothesis ( 20 ). Two studies with larger cohorts have been recently published using the Infinium MethylationEPIC BeadChip ( 21 , 22 ), which covers 850 000 CpG sites. Fragoso-Bargas et al ( 22 ) identified 4 CpG sites associated with BMI and hyperglycemia in peripheral blood leukocytes of a subcohort of the EPI-PREG study; however, the data were not validated in an independent cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most studied epigenetic mechanisms is DNA methylation, which plays an important role in normal development, chromatin organization and gene expression [3]. Several studies have indicated that DNA methylation is associated with cardiovascular risk factors such as body mass index (BMI) [4][5][6][7], gestational diabetes (GDM) [8], type 2 diabetes (T2D) [9][10][11][12][13], lipid levels [14,15], hypertension [16,17], smoking [18][19][20][21][22] and alcohol intake [23][24][25], suggesting that cardiometabolic diseases have an epigenetic component.…”
Section: Introductionmentioning
confidence: 99%